Obliczanie Powłok Translacyjnych Metodą Wieloboku Sznurowego - Pełka, Z. (Engineering Transactions, 1959)
The solution of the basic differential equation of a translational shell, in a closed form or by means of rapidly convergent series, has been obtained only in certain particular cases of shell and load. In numerical solutions the finite difference method has been the only method hitherto used. The author uses the method of funicular polygon. After quoting the principal equations of this method the equation is derived expressing the relation between the stress-function F and the magnitude of the stress Z at the nodes of the net. The right-hand member of this equation contains the values of the load at 9 neighbouring nodes, therefore the procedure described may take into account even a marked variability of Z. For an elliptical parabola, this equation takes a very simple form. The method described is used to solve a numerical problem. The results obtained are compared with those obtained by means of the analytical method and by the method of finite differences. The method of funicular polygon gives greater accuracy than that of finite differences. The possibility of application of the two numerical methods to the computation of translational shells is discussed in a general manner.